Entrepreneurial Success Examined through Social Capital and Entrepreneurial Competence among MSME Operators in the PTB Tourist Attraction in Maros City - Irwan Abdullah; Firdaus, Ahmad; Nur Sandi Marsuni; Kahar (Economos : Jurnal Ekonomi dan Bisnis, 2023)
One area in South Sulawesi Province, precisely in the capital city of Maros Regency, has a downtown tourist attraction known as "Pantai Tak Berombak" (PTB), which stands as one of the iconic landmarks of the Regency. In this tourist attraction, many Micro, Small and Medium Enterprises (MSMEs) operate. These business operators play an important role in the success of their ventures, as they are the driving force behind business operations. Many factors are associated with influencing entrepreneurial success. Among these factors are aspects derived from the entrepreneur himself, including the social capital possessed by the business operators and their entrepreneurial competence. This research will be carried out at PTB (Undulating Beach) Maros City with an estimated time of 12 months. The population in this study of all MSME actors in PTB tourist attractions amounted to 165 MSMEs and to obtain samples, sampling was carried out using simple random sampling techniques. The sample in this study was 117 MSMEs located in the PTB area of Maros City. For research data collection instruments using questionnaires, this technique uses a likeart scale. The results showed that: 1) the picture of social capital is generally categorized as low, the picture of entrepreneurial competence is generally categorized as high and the picture of entrepreneurial success is generally categorized as high. 2) the simultaneous influence of social capital and entrepreneurial competence on entrepreneurial success in MSME actors in PTB Maros City tourist attractions, the magnitude simultaneously is 41%. 3) there is a positive and significant influence of social capital on the success of entrepreneurship in MSME actors in PTB Maros City tourist attractions, and 4) there is a positive and significant influence of entrepreneurial competence on entrepreneurial success in MSME actors in PTB Maros City tourist attractions.